PENGARUH PERMAINAN PVC (Polyvinyl Chloride) PIPE SAND AND WATER TABLE TERHADAP KEMAMPUAN SAINS PERMULAAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 1 KOTA PEKANBARU - Fatimah Adriani; Daviq Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on early childhood science skills have not developed optimally. So it is necessary to apply the use of PVC (Polyvinyl Chloride) pipe sand and water table. This study aims to determine the effect of PVC (Polyvinyl Chloride) pipe sand and water table game against the early science ability of children aged 4-5 years in TK Negeri Pembina 1 Pekanbaru City. The sample used in this study were 18 children. The data collection technique used is the observation sheet. Technique of data analysis using t-test test by using program of SPSS 18. The research hypothesis is the use of PVC (Polyvinyl Chloride) pipe sand and water table has an influence on the early science ability of children aged 4-5 years in TK Negeri Pembina 1 Pekanbaru City. This can be known from the analysis of data obtained tcount = 16,171 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a significant difference in early childhood science ability after using PVC (Polyvinyl Chloride) pipe sand and water table in learning. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying PVC (Polyvinyl Chloride) pipe sand and water table. The influence of PVC (Polyvinyl Chloride) pipe sand and water table on the early science of children aged 4-5 years in TK Negeri Pembina 1 Pekanbaru City is 54.41%.Keywords: Science Ability of the Beginning, PVC (Polyvinyl Chloride) Pipe Sand and Water Table Games